Regulation of epithelial cell expressed C3 in the intestine – Relevance for the pathophysiology of inflammatory bowel disease?. (October 2017) - Sünderhauf, Annika; Skibbe, Kerstin; Preisker, Sophie; Ebbert, Karen; Verschoor, Admar; Karsten, Christian M.; Kemper, Claudia; Huber-Lang, Markus; Basic, Marijana; Bleich, André; Büning, Jürgen; Fellermann, Klaus; et al.
Highlights: C3 levels are upregulated in intestinal epithelial cells in a chronic DSS-colitis model. C3a improves LPS triggered pro-inflammatory response of IEC. Commensal bacteria regulate C3 expression levels in ileal and colonic pIECs. C3 and CFB are upregulated in inflamed tissue from CD but not UC patients. Abstract: The complement system not only plays a critical role in efficient detection and clearance of bacteria, but also in intestinal immune homeostasis as mice deficient for key complement components display enhanced intestinal inflammation upon experimental colitis. Because underlying molecular mechanisms for this observation are unclear, we investigated the crosstalk between intestinal epithelial cells (IEC), bacteria and the complement system in the course of chronic colitis. Surprisingly, mouse intestinal epithelial cell lines constitutively express high mRNA levels of complement component 3 (C3), Toll-like receptor 2 (Tlr2) and Tlr4. Stimulation of these cells with lipopolysaccharide (LPS), but not with flagellin, LD-muramyldipeptide or peptidoglycan, triggered increased C3 expression, secretion and activation. Stimulation of the C3aR on these cell lines with C3a resulted in an increase of LPS-triggered pro-inflammatory response. Tissue biopsies from C57BL/6J mice revealed higher expression of C3, Tlr1, Tlr2 and Tlr4 in colonic primary IECs (pIECs) compared to ileal pIECs, while in germ-free mice no differences in C3 protein expression was observed. In DSS-induced chronic colitis mouse models, C3 mRNA expression was upregulated in colonic biopsies and ileal pIECs with elevated C3 protein in the lamina propria, IECs and the mucus. Notably, increased C3b opsonization of mucosa-attached bacteria and decreased fecal full-length C3 protein was observed in DSS-treated compared to untreated mice. Of significant interest, non-inflamed and inflamed colonic biopsy samples from CD but not UC patients displayed exacerbated C3 expression compared to controls. These findings suggest that a novel TLR4-C3 axis could control the intestinal immune response during chronic colitis.